Threats, Dynamics, Nationalism And Strategies: A Study of Indonesian Border in West Kalimantan - Jagad Aditya Dewantara; Dasim Budimansyah; Cecep Darmawan; Kokom Komalasari; Efriani Efriani (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
This article reviews border issues related to threats, dynamics, problems, and nationalism of the Indonesian people living on the border of West Kalimantan. The dynamics and complex problems on the Indonesia-Malaysia border have created various conflicts and struggles for citizenship in both countries. In addition, kinship in the two countries has a different impact on nationalism, as people on the border in the PLBN zone are more controllable from a socio-economic point of view. Meanwhile, people living in non-PLBN zones tend to have many problems, such as poor welfare and infrastructure development. As a result, the Indonesian people, bordered by the Non-PLBN zone, seem to prefer a country that provides welfare. This study uses the civic engagement and securitization theory to analyze how these issues occur in the Indonesian-Malaysian border community. This study shows a critical review of the picture related to threats, dynamics, nationalism, and strategies of local communities at the border. In the case study, issues concerning the dynamics of local border residents in Indonesia are themes that deserve more attention from various parties, from academics to practitioners. Therefore, with empirical evidence from this study, it is hoped that researchers, academics, practitioners, and politicians will be able to respond wisely to cross-border dynamics